Erectile Dysfunction Among Patients on Methadone Maintenance Therapy and Its Association With Quality of Life. Issue 1 (January 2017) - Teoh, Joni Bing Fei; Yee, Anne; Danaee, Mahmoud; Ng, Chong Guan; Sulaiman, Ahmad Hatim Bin
Abstract : Objectives: Erectile dysfunction (ED) is a problem commonly encountered by patients on methadone maintenance therapy (MMT). This study aimed to assess the prevalence of ED among this group of patients along with its risk factors and association with quality of life (QOL). Methods: Male patients on MMT in a tertiary hospital in Malaysia were included in the study. A total of 134 patients with sexual partners were assessed for ED using the International Index of Erectile Function. Patients were assessed for substance use using Opiate Treatment Index (OTI) and depression using the Malay version of the self-rated Montgomery-Asberg Depression Rating Scale (MADRS-BM). QOL was evaluated using World Health Organisation Quality of Life (WHOQOL)-BREF. Results: The prevalence of ED among patients on MMT was 67%, with 26.1% having mild ED, 30.4% having mild-to-moderate ED, 7.0% having moderate ED, and 17.2% having severe ED. Patients with depression were 4 times more likely to have ED compared with patients without depression, whereas increasing age significantly correlated with the severity of ED. Having ED predicted a poorer QOL in the social relationships domain. Conclusion: Depression is highly associated with ED, which negatively influences the social aspect of QOL among patients on methadone maintenance therapy.